TRAFFIC MANAGEMENT BASED ON POWER RELATIONS OF TRAFFIC FLOW AND ROAD - Vladimir Alekseevich Trubitsyn; Denis Ivanovich Golub (Вестник Северо-Кавказского федерального университета, 2022)
New indicators of efficiency of traffic are presented: traffic capacity, capacity of the road, capacity factor of the road. The methods of traffic management on the basis of the developed indicators.